Validation of the human disharmony loop: Pectoralis minor tenotomy significantly reduces pain and improves function in historically challenging patients who meet reproducible and explicit diagnostic criteria - James M. Friedman; Jaicharan Iyengar; Ketan Sharma (PLoS ONE, 2025)
Background/Objectives Patients commonly present with a mix of intractable shoulder pain, persistent impingement/loss of shoulder motion, neck pain, headaches, and distal neuropathy. These patients are notoriously resistant to surgical and non-surgical treatments. Previously we proposed the Human Disharmony Loop (HDL) as a model that anatomically explains these symptoms and diagnostically predicts successful response to surgical intervention. The purpose of this study is to validate positive surgical treatment outcomes in patients diagnosed in the HDL via retrospective chart review. We hypothesized that pectoralis minor release would reliably decrease pain and occipital headaches and increase shoulder motion for patients who met diagnostic criteria for the HDL. Methods Patients diagnosed with the HDL and treated with pectoralis minor release at two separate institutions with at least 6-month follow-up were included. Diagnosis was based on explicit anatomic and symptomatic criteria: coracoid tenderness, scapular protraction, and at least one end symptom. Neuropathy was tested using the scratch-collapse test. Outcomes included pain scores, clinical neuropathic lesions, rotator cuff impingement signs, shoulder range of motion, and complications. Results 115 patients were included. Average age was 48. 37% were male. 89% of patients who received a preoperative subcoracoid injection reported a significant decrease in presenting symptoms. 6 months after PM release, median VAS pain scores decreased from 8 to 2. Occipital headaches decreased from 66% to 6%. Rotator cuff impingement decreased from 87% to 10%. Median shoulder abduction increased from 90 to 180 degrees. Neuropathy decreased at the following locations: scalenes 57–2%, suprascapular 51–0%, quadrilateral 81–5%, radial 60–11%, cubital 31–25%, carpal 53–25%. 25% of patients required secondary distal neurolysis. Complications remained low at 3% (3 seroma, 1 wound dehiscence). Conclusions Patients diagnosed with the Human Disharmony Loop exhibit a dramatic clinical improvement following pectoralis minor release. A medial coracoid pectoralis minor block injection can aid in diagnosis but does not rule-out the syndrome. Patients showed significant reductions in shoulder pain, headaches, concomitant neuropathic lesions and improved shoulder range of motion. Patients should be counseled that some may need secondary neurolysis for residual neuropathy.